Superior mesenteric venous thrombosis complicating acute appendicitis: A case report. Issue 25 (June 2018) - Gad, AbdAllah; Hindi, Zakaria; Zahoor, Talal; Zock, Rémy Zock À
Abstract: Rationale: Superior mesenteric venous thrombosis (SMVT) is a rare condition that carries high mortality. Very few cases have been reported of SMVT, complicating acute appendicitis. Early recognition requires a high index of suspicion and is crucial in successful treatment of such a life-threatening condition. Patient concerns: A 33-year-old male presents with a 4-day history of right lower abdominal pain, nausea and subjective fever. CT scan showed acute appendicitis and a central filling defect in the superior mesenteric vein. Diagnoses: Acute appendicitis complicated by SMVT. Interventions: Intravenous antibiotics, appendectomy, and anticoagulation. Outcomes: Repeat CT scan showed successful resolution of the SMVT at a 3-month follow up. Lessons: Clinical awareness and high index of suspicion are essential to diagnose and manage SMVT, a serious complication of acute appendicitis.